Preventing diarrhoea in enteral nutrition: the impact of the delivery set hang time. Issue 8 (4th May 2015) - Arevalo‐Manso, J. J.; Martinez‐Sanchez, P.; Juarez‐Martin, B.; Fuentes, B.; Ruiz‐Ares, G.; Sanz‐Cuesta, B. E.; Parrilla‐Novo, P.; Diez‐Tejedor, E.
Summary Background To meet the current recommendations for enteral tube feeding (ETF), we updated our previous practice in 2011 and began to use a 24‐h delivery set hang time (DSHT). We evaluated the impact of this update on the risk of diarrhoea and in diarrhoea‐free survival. Methods Observational, retrospective study with historical controls on ischaemic and haemorrhagic stroke patients undergoing ETF. Diarrhoea occurrence (≥ 3 liquid stools in 24 h) was compared between patients with a 24 h DSHT (2011–2014) and a 72/96 h DSHT (2010–2011). The analysis was conducted using Kaplan–Meier curves and a Cox regression model. Results A total of 175 patients were included [median age 81 years (IQR = 12), 46.9% males], 103 in the group with a 24 h DSHT and 72 in the group with a 72/96 h DSHT. The group with a 24 h DSHT had a lower diarrhoea frequency (13.6% vs. 34.7%, risk ratio: 0.39, 95% CI: 0.22–0.70, p = 0.001) and a lower diarrhoea incidence rate (0.87 vs. 2.32 cases of diarrhoea/100 patient*day, rate ratio: 0.37, 95% CI: 0.19–0.72, p = 0.004). The Kaplan–Meier curves showed a longer diarrhoea‐free survival for this group (p = 0.003, log‐rank test). A 24 h DSHT was associated with a lower risk of diarrhoea (HR = 0.27, 95% CI: 0.12–0.61, p = 0.002), adjusted by albumin, stroke severity, intravenous thrombolysis, the administration of clindamycin and cefotaxime, and the administration of an enteral formula for diabetic patients. Conclusions The 24 h DSHT was independently associated with a lower risk of diarrhoea and longer diarrhoea‐free survival in hospitalised patients with acute stroke under ETF, compared with a 72/96 h DSHT.